Métrica produto torcido e variedades de curvatura negativa - Santos, Aderval Alves dos (2015)
This work, based on the articles M. Brozos Vazquez, E. Garcia-Rio and R. Vazquez- Lorenzo whose goal is to build examples of manifolds locally conformally flat full of negative curvature through warped product and multiply warped product structure. The warped product was first introduced by Bishop and O’Neill, who modified the structure of the Riemannian product in obtaining new manifolds of negative curvature.